2019
DOI: 10.1515/cclm-2019-0899
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining information from the brain in a non-invasive way: determination of iron in nasal exudate to differentiate hemorrhagic and ischemic strokes

Abstract: BackgroundDifferentiation between hemorrhagic and ischemic stroke is currently made by brain imaging or analyzing blood and cerebrospinal fluid (CSF) samples. After describing a new drainage route from brain to nasal mucosa, nasal exudate samples can be considered a new and promising source of biomarkers. Saliva can also be evaluated.MethodsWe determined iron in nasal exudate and saliva samples from patients of acute stroke during the first 48 h from onset. A simple, non-invasive sampling procedure was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Twenty of the study patients were included in a previous publication [16]; we found similar trends in subjects who did not take part of the previous study (nasal exudate iron concentration: 0.103 ± 0.010 nmol/mg in the IS group vs. 0.480 ± 0.050 nmol/mg in the HS group p < 0.0001). These concentration differences were not found in the levels of iron in blood (IS 58.38 mcg/dL and HS 66.05 mcg/dL p = 0.323).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Twenty of the study patients were included in a previous publication [16]; we found similar trends in subjects who did not take part of the previous study (nasal exudate iron concentration: 0.103 ± 0.010 nmol/mg in the IS group vs. 0.480 ± 0.050 nmol/mg in the HS group p < 0.0001). These concentration differences were not found in the levels of iron in blood (IS 58.38 mcg/dL and HS 66.05 mcg/dL p = 0.323).…”
Section: Resultssupporting
confidence: 73%
“…The chance of studying cerebral lymphatic drainage opens up new expectations in this field. Our group performed a previous pilot study which suggested that measurement of iron in nasal secretion was feasible and could distinguish between IS and HS [16]. Our objective was to confirm our previous findings in a bigger sample of stroke patients.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The authors were able to differentiate patients that had suffered from hemorrhagic stroke compared with ischemic stroke by the amount of iron in the nasal exudate. Although this study was preliminary, consisting of samples from only 20 patients, it serves as in vivo clinical evidence that CSF waste products may be cleared through nasal pathways, at least during pathological conditions [246].…”
Section: Evidence From Humansmentioning
confidence: 99%